Biliary cystadenoma in a male domestic Dutch rabbit (Oryctolagus cuniculus). Issue 1 (25th February 2014) - Sabater, Mikel; Mancinelli, Elisabetta; Stidworthy, Mark Frederick
Abstract : A two‐year‐old castrated male Dutch rabbit ( Oryctolagus cuniculus ) was referred due to acute onset of anorexia. A firm, non‐painful, round, approximately 10 cm diameter mass was palpated in the left cranial abdomen. No other major abnormalities were identified during physical exam. Radiography and ultrasonography characterised the mass. Exploratory laparotomy revealed a pedunculated mass attached to the quadrate hepatic lobe which was removed without complications. Histopathology confirmed the complete removal of a mass identified as hepatic biliary cystadenoma not showing evidence of malignancy or intra‐hepatic dissemination. The rabbit was healthy on further rechecks up to one year later. This is the second reported case of diagnosis and successful removal of a biliary cystadenoma in a rabbit with the peculiarity of this patient being a male rabbit. Biliary cystadenoma should, therefore, be part of the differential diagnosis of hepatic neoplasia in male domestic rabbits.